Risk Factors Affecting Carpal Tunnel Syndrome in Women Laborer of Tobacco Warehouse Ajung District, Jember - Dasarina Rizqi Amalia; Ida Srisurani Wiji Astuti; Yudha Nurdian (Faculty of Medicine, University of Jember, 2019)
Carpal Tunnel Syndrome frequently experienced by workers whose daily activities always use repetitive movements on the wrist. Carpal Tunnel Syndrome is a syndrome that can actually be prevented because there is no risk factor that can’t be changed except the age factor. Previous research has shown a fairly high prevalence about 42%-93% in factory workers. This study aims to determine the factors that affect the occurence of Carpal Tunnel Syndrome in women workers warehouse tobacco. This is an analytical observational study with cross sectional study design which using 50 samples who met inclusion and exclusion criteria. Instrument in this research is clinical questionnaire to diagnose CTS and Phalen test. Spearman correlation test result obtained long working p=0,036, r=0,298 and pain intensity p= <0,01, r=0,635 which means there is significant correlation with moderate strength between length of work with CTS and strong correlation between the intensity of pain with CTS. Keywords: Carpal Tunnel Syndrome, risk factor, women laborer